10.1016/s1541-9800(10)70340-9 (CrossRef Listing of Deleted DOIs, 2000)
Objectives To evaluate the performance and reader-dependent variability of the VISITECT CD4 lateral flow assay (LFA) as a screening tool for identifying advanced HIV disease (AHD; CD4 ≤ 200 cells/μL) during routine programmatic implementation. Methods We conducted a two-phase diagnostic evaluation in Argentina, including a training phase (n = 100) and a validation phase (n = 249), for a total of 349 participants, comparing VISITECT CD4-LFA with flow cytometry. Diagnostic performance was assessed using the manufacturer-recommended cut-off. Sensitivity, specificity, and accuracy were calculated with 95% confidence intervals (CI). Receiver operating characteristic (ROC) analysis was used to estimate the implicit CD4 thresholds applied by readers. Results The VISITECT CD4-LFA showed 100% sensitivity (95% CI 94-100) in both phases. Specificity improved from 19% (95% CI 8-35) to 40% (95% CI 31-49) after training, with accuracy increasing from 42% (95% CI 33-53) to 57% (95% CI 51-63). ROC analysis demonstrated a shift in the implicit reader threshold from 363 to 270 cells/μL, indicating improved interpretation with experience. Conclusions The VISITECT CD4-LFA is a highly sensitive point-of-care (POC) tool for AHD screening, though its visual design limits specificity, highlighting the need for reader-independent technologies.